Interactive Content: Engaging Audiences in a Distracted World - Susanti, Erna; Apriyanti , Nike; Harisriwijayanti , Harisriwijayanti (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2024)
This study investigates the dynamics of audience engagement on the Shopee platform, focusing on Interactivity Level, Content Quality, User Attention, and Audience Engagement. Using a quantitative approach with a sample of 100 users and employing Structural Equation Modeling (SEM) with Smart PLS, the research examines direct and indirect relationships among these variables. The findings reveal significant direct effects of Interactivity Level and Content Quality on Audience Engagement, highlighting the importance of interactive features and high-quality content in driving engagement. Additionally, User Attention emerges as a critical mediator, enhancing the impact of Interactivity Level and Content Quality on Audience Engagement. Specifically, higher Interactivity Level and superior Content Quality increase User Attention, leading to heightened Audience Engagement. These insights underscore the strategic significance of optimizing interactive elements and content quality to capture and sustain user attention effectively in competitive e-commerce environments. The study contributes valuable implications for enhancing digital marketing strategies and improving user experience on platforms like Shopee, aiming to foster greater user satisfaction, loyalty, and business success.